Agrobacterium Transformation of Tea Plants (Camellia sinensis (L.) KUNTZE): A Small Experiment with Great Prospects - Anastasia Fizikova; Elena Subcheva; Nikolay Kozlov; Varvara Tvorogova; Lidia Samarina; Ludmila Lutova; Elena Khlestkina (Plants, 2024)
Tea has historically been one of the most popular beverages, and it is currently an economically significant crop cultivated in over 50 countries. The Northwestern Caucasus is one of the northernmost regions for industrial tea cultivation worldwide. The domestication of the tea plant in this region took approximately 150 years, during which plantations spreading from the Ozurgeti region in northern Georgia to the southern city of Maykop in Russia. Consequently, tea plantations in the Northern Caucasus can serve as a source of unique genotypes with exceptional cold tolerance. Tea plants are known to be recalcitrant to Agrobacterium-mediated transfection. Research into optimal transfection and regeneration methodologies, as well as the identification of tea varieties with enhanced transformation efficiency, is an advanced strategy for improving tea plant culture. The aim of this study was to search for the optimal Agrobacterium tumefaciens-mediated transfection protocol for the Kolkhida tea variety. As a result of optimizing the transfection medium with potassium phosphate buffer at the stages of pre-inoculation, inoculation and co-cultivation, the restoration of normal morphology and improvement in the attachment of Agrobacterium cells to the surface of tea explants were observed by scanning electron microscopy. And an effective method of high-efficiency Agrobacteria tumefaciens-mediated transfection of the best local tea cultivar, Kolkhida, was demonstrated for the first time.